Endogenous preferences : survey notes on the demand-theoretic implications of a class of nonstandard consumer preference specifications - Van Aswegen, Victor (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1987.